2012
DOI: 10.1007/s00520-012-1485-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differentials in mental health needs and service utilization among persons with cancer

Abstract: Despite methodological limitations, findings confirm past research showing that disadvantaged ethnic minorities may receive differential recommendations for mental health problems among persons with cancer. This may contribute to the differential treatment gap in mental health care among persons with cancer of contrasting ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The suicide rate for persons with cancer is estimated to be twice the rate in the general US population . Similar higher risk was documented in other countries such as Sweden and Israel . Suicidality can include suicidal ideation (ie, thoughts of ending one's own life), suicidal attempts (ie, trying to take one's own life), and suicidal acts (ie, taking one's own life).…”
Section: Introductionmentioning
confidence: 78%
“…The suicide rate for persons with cancer is estimated to be twice the rate in the general US population . Similar higher risk was documented in other countries such as Sweden and Israel . Suicidality can include suicidal ideation (ie, thoughts of ending one's own life), suicidal attempts (ie, trying to take one's own life), and suicidal acts (ie, taking one's own life).…”
Section: Introductionmentioning
confidence: 78%
“…Actions to bridge the gap through improved availability and accessibility of the services and the reduction of the subjective barriers such as stigma would facilitate access to the benefits derived from evidence‐based mental health treatments in both primary care and/or in specialized services . Also, for a more complete remedy of the situation, specific training should be made available for the medical staff in identifying and treating the comorbid mental disorders and, wherever possible, to include specialized mental health providers as an integral part of the multidisciplinary team caring for person with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Psycho‐oncological research has shown similar treatment gaps for mental disorders among persons with cancer . For example, a US community‐based study found that only 35% of cancer survivors who reported mental problems accessed specialized services .…”
Section: Introductionmentioning
confidence: 99%